Reduction of Preoperative Anxiety in Patients Undergoing General Anesthesia Using Combined Finger Hold Technique and Deep Breathing Relaxation - Hilda Arifiah; Suanda Saputra; Lido Sianipar; Deni Alamsah (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2026)
Preoperative anxiety is a common psychological condition experienced by patients before surgery and may negatively affect the anesthetic process and postoperative recovery. This condition can increase anesthetic requirements, cause hemodynamic instability, and delay recovery. Non-pharmacological interventions, such as the combination of the finger hold technique and deep breathing relaxation, may help reduce anxiety. This study aimed to analyze the effect of the combination of the finger hold technique and deep breathing relaxation on preoperative anxiety levels in patients undergoing general anesthesia at RSUD Kabupaten Bekasi. A quantitative study with a quasi-experimental one-group pretest–posttest design was conducted. A total of 40 respondents were selected using purposive sampling. Anxiety levels were measured using The Amsterdam Preoperative Anxiety and Information Scale (APAIS). Data were analyzed using the Marginal Homogeneity test. Before the intervention, most respondents experienced severe anxiety (70.0%). After the intervention, the majority showed a decrease in mild anxiety (92.5%). Statistical analysis revealed a significant difference in anxiety levels before and after the intervention (χ² = 106.000; p < 0.001). The combination of the finger hold technique and deep breathing relaxation is effective in reducing preoperative anxiety and can be considered a simple and practical non-pharmacological intervention in preoperative nursing care.